Organizational structure and the hold-up problem - Vinicius Carrasco (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
In this note, I consider a setting in which an agent can exert costly unobservable effort towards two activities and is, a priori, uncertain about its ability to perform them. A (non-contractible) ability enhancing investment can be performed. The lack of commitment from a Principal concerned with (informational) rent extraction, and who is in control of both activities, induces the standard underinvestment outcome of Hold-Up problems. It is then shown that, if the two activities are assigned to two different Principals, ex-post incentives will be more powerful generating, from an ex-ante perspective, higher incentives for ability enhancing investment. The combination of higher ex-ante investments and expost incentives produces an outcome that is superior than a single Principal's outcome in terms of efficiency. This suggests that organizational structure, through its influence on the design of incentives over contractible variables, can play a key role is solving Hold-Up problems.
Keywords: 330